Friction stir welding of carbon black reinforced high-density polyethylene tube-to-tubesheet joints - Syed Haris Iftikhar; Abdel-Hamid Ismail Mourad; Dinu Thomas Thekkuden; Nizamudeen Cherupurakal; R. Krishnapriya (International Journal of Lightweight Materials and Manufacture, 2023)
Industrial heat exchanger applications dealing with highly corrosive fluids demand the use of thermoplastic heat exchangers because of the chemically inert and anti-fouling nature of the thermoplastics. A non-conventional joining framework, based on the friction stir welding (FSW) technique, is used to form high-quality thermoplastic tube-to-tubesheet joints (TTJs). The proposed technique has potential applications for thermoplastic shell-and-tube heat exchangers and piping industries (as flange-to-pipe joints). In this work, the tube and tubesheet materials made of carbon black reinforced high-density polyethylene were used. The effect of different FSW parameters (rotational speed, plunge depth, tube protrusion, dwell time) on the tube pull-out behavior was investigated. The FSW technique showed capabilities at a wide range of operating conditions. The highest load bearing capacity of 517 N was achieved using the FSW process, much higher than adhesive joints. Also, it provides higher extensions at maximum load than adhesive joints, with the highest extension of 5.161 mm. Two FSW cases provided high leak paths of 77% and 58% remaining sheet thickness (greater than tube thickness) along with high load bearing capacity and corresponding extensions. The macroscopic and SEM-based fractographic studies illustrated three types of failure behavior: ductile, brittle, or mixed depending on the FSW process conditions. The DSC results showed no significant crystallinity changes in the weld material. The TGA results showed no significant thermal degradation occurring in the weld material. Further, the FTIR analysis indicated possible oxidation of the weld material. The capability to form TTJs with high leak path, high load bearing capacity, and no significant material degradations makes the FSW technique suitable for thermoplastic shell-and-tube heat exchanger applications.